Body image, emotional intelligence and quality of life in peritoneal dialysis patients - Eleni Marki; Ioannis Moisoglou; Stamata Aggelidou; Maria Malliarou; Konstantinos Tsaras; Ioanna V. Papathanasiou (AIMS Press, 2023)
Background: End-stage-renal-disease is one of the most common chronic diseases, and peritoneal dialysis constitutes one of the replacement therapies. The aim of this study was to investigate the views of patients on peritoneal dialysis regarding their body image, to assess their quality of life and level of emotional intelligence. Methods: A cross-sectional study was performed with structured questionnaires. The sample of the study was the patients undergoing peritoneal dialysis and monitored by the nephrology clinics of 7 public hospitals in Greece. Results: A total of 102 completed questionnaires were collected and analyzed (68% response rate). The participants showed moderate degree of body-image dysphoria (mean = 1.29, SD = 0.94), moderate levels of emotional intelligence and experienced moderate quality of life. According to the statistical analysis, women reported worse body image (p = 0.013) and university graduates showed higher levels of emotionality (p = 0.016). The correlations between the quality of life questionnaire subscales and demographic characteristics revealed statistically significant relationships between marital status and the Physical Functionality subscale, where unmarried people had a better quality of life in this subscale (p = 0.042) and between postgraduate/doctoral degree holders and the subscale Patient Satisfaction (p = 0.035). Also, statistically significant relationships were found between occupation and the Social Interaction subscale, where those engaged in household activities and were unemployed (p = 0.022) showed better quality of life. Participants living in semi-urban areas had better quality of life on the subscale Burden of Kidney Disease (p = 0.034). Conclusion: ESRD patients on peritoneal dialysis suffer significant limitations related to disease and treatment modality. According to our findings, these affect both their body image as well as their quality of life. Improvement in emotional intelligence is the factor which plays an important mediating role in improving both body image and quality of life in patients on peritoneal dialysis.